Unveiling the 'Pesantrenpreneur' Phenomenon: Nurturing Entrepreneurship within Islamic Boarding Schools - Wahana, Akbar Nuur Purnama Darma; Ahmad Muktamar B; Rukmana, Arief Yanto (Westscience Press, 2023)
This research explores the burgeoning phenomenon of 'Pesantrenpreneurship' within an Islamic boarding school in West Java, Indonesia. 'Pesantrenpreneurs' are individuals who engage in entrepreneurial activities within the context of the pesantren, blending religious values with innovative business pursuits. Through a mixed-methods approach involving qualitative interviews and quantitative surveys, this study uncovers the driving factors behind 'Pesantrenpreneurship,' the types of businesses emerging, the impact on personal development and the community, and the intersection of religious values and entrepreneurship. The findings contribute to our understanding of the evolving role of religious institutions in promoting entrepreneurship and fostering socially responsible business practices.